Controle postural durante o movimento sentado para de pé em crianças e adolescentes com síndrome de Down e fatores biopsicossociais - Oliveira, Maria Fernanda Pauletti (2018)
Down syndrome (DS) is a health condition that causes changes in neuromotor, sensory, cognitive and musculoskeletal, compromising postural control and adaptive success in tasks. The health condition of the individual according to the International Classification of Functioning, Disability and Health (ICF) model results from the relationship between the integrity of body functions and structures, capacity to perform functional activities and social participation, as well as the influence of contextual factors. Acknowledging the importance of evaluating all ICF domains to understand postural control in DS and the possible interactions between them motivated Study I, titled "Postural control in children and adolescents with Down syndrome and relations with the dimensions of the International Classification of Functioning - A Systematic Review". This study aimed to understand postural control in children and adolescents with DS, to verify the methods used in the literature considering the ICF dimensions, to evaluate the quality of the studies, and to describe the main results. Changes in postural control in individuals with DS and a lack of research addressing postural control in DS during dynamic activities and postural transfers, such as the to sit to stand movement (STS) were found. There was also a lack of studies addressing the relations between the ICF domains. These findings motivated the study II - "Postural oscillation during sit to stand movement and associations with biopsychosocial aspects in children and adolescents with Down syndrome". The study sought to compare the postural oscillation during the execution of the STS movement in children and adolescents with DS and with typical individuals of 7 to 14 years of age (mean 10,23 ±2,36) of both sexes, based on the analysis of the behavior of the pressure center (CoP). It also aimed to identify specific disabilities in body structure and function, limitations in activities and participation, and contextual factors that would be associated with the performance of the STS movement. We found that children and adolescents with DS had postural oscillation that was greater and faster than their typical peers during STS movement. The main predictors of postural oscillation in this movement were hypotonia and quadriceps muscle strength. It was also noted that gross motor function, functional balance and the characteristics of the domestic environment were related to body structure and function components, such as hypotonia, quadriceps muscle strength, and postural oscillation during STS movement. Thus, it is important to consider all ICF domains in therapeutic approaches to obtain a biopsychosocial panorama of an individual.